2018
DOI: 10.1159/000488061
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autologous Platelet Concentrates in Alveolar Socket Preservation: A Systematic Review

Abstract: Prevention of alveolar bone resorption after tooth extraction may be useful for implant rehabilitation of the edentulous site minimizing the future need for bone augmentation procedures. A number of studies have investigated the efficacy of autologous platelet concentrates for the preservation of the alveolar bone volume after tooth extraction. Although encouraging results have been published, the available data are still controversial. The aim of the present systematic review was to assess the effect of plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…In most of these studies, the use of PRF was clearly beneficial [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], while in others the utility of PRF seemed to be more controversial, failing to show enhancement of the socket healing process [ 31 , 32 , 33 ]. In recent systematic reviews, definitive conclusions could not be drawn [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies, the use of PRF was clearly beneficial [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], while in others the utility of PRF seemed to be more controversial, failing to show enhancement of the socket healing process [ 31 , 32 , 33 ]. In recent systematic reviews, definitive conclusions could not be drawn [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of low-cost and minimally invasive therapies for orthopedics has led to the use of biological therapies, especially platelet-rich plasma (PRP), to optimize clinical outcomes and improve tissue recovery 5. Studies on the therapeutic applications of PRP have been conducted in several fields, such as maxillofacial surgery 6, cardiovascular surgery 7, and plastic surgery 8. In orthopedics, the clinical indications include hip and knee osteoarthritis, rotator cuff pathologies 8, epicondylitis and tendinitis 9, fracture healing 10, and back pain 11.…”
Section: Introductionmentioning
confidence: 99%
“…As a high concentration of platelets is achieved in PRP, a high concentration of growth factors such as epithelial growth factor, transforming growth factor, and the platelet-derived growth factor is added to the local milieu, which helps drive the regenerative mechanism. [ 15 16 17 ] Burmeister et al . in their in vitro studies have demonstrated that autologous platelet concentrate promotes better growth and migration of Muller cell compared to both control and serum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully utilized in the fields of plastic, cosmetic, reconstructive, oral, and orthopedic surgery. [ 15 16 17 ] Although the use of platelets for the treatment of MH has previously been reported, literature lacks studies comparing its efficiency with inverted ILM flap in large MH. [ 5 18 19 20 21 22 ]…”
mentioning
confidence: 99%